Retrospective renal sonographic study: assessment of renal volume and resistance index - Denova, L.D.; Ivanov, D.D.; Shukht, O.Y. (KIDNEYS, 2024)
Background. Renal ultrasound is a convenient, safe, and affordable tool for visualization of the kidneys in the daily practice of nephrologists and doctors of other specialties. Kidney volume, which is calculated by the sonographic method, gives an idea about the state of the kidneys of the patient, but says almost nothing about their function. There are many studies of renal index of resistance (IR) as a marker of kidney function. IR values were compared with serum creatinine levels and/or histological data. And although conflicting research data limit the use of IR as a marker of kidney function, correct interpretation of IR helps restore it to the status of a candidate marker of kidney function. The purpose of the study: to conduct a retrospective analysis of the sonographic renal parameters in patients who sought outpatient medical care at the Brovary medical institution. Materials and methods. Retrospective randomized cohort study was conducted of sonograms of 66 outpatients who sought outpatient medical care at a private medical facility in Brovary from February 2022 to February 2024. They were divided into 2 groups: the first one (n = 31) — men and the second group (n = 35) — women. Results. The results of multiple linear regression in the group 1 for right kidney (RK) showed that the independent variable in this model, RK thickness, is of low significance as a predictor for IR RK, and the following independent variables were not significant as predictors for IR RK: RK length, RK width, RK volume, age. Multiple linear regression results in the group 1 for left kidney (LK) indicate that the independent variable in this model, LK width, is moderately significant as a predictor for LK IR, and the following independent variables were not significant as predictors for LK IR: LK length, LK thickness, LK volume, age. Multiple linear regression results in the group 2 for RK showed that the independent variables in this model, RK width and age, are significant as predictors for IR RK, and the following independent variables were not significant as predictors for IR RK: RK length, RK thickness, RK volume. Multiple linear regression results in the group 2 for LK indicate that the independent variable in this model, LK width, is moderately significant as a predictor for LK IR, and the following independent variables were not significant as predictors for LK IR: LK length, LK thickness, LK volume, age. Conclusions. Renal ultrasound allows predicting the category of patients who will need a consultation with a nephrologist/urologist, identifying risk groups for chronic kidney disease.